Improving Vocabulary Achievement Through Lyric Song - Khalisa, Halwa; Rahmadewi, Alfina; Nasution, Khayla Rahmadani; Rahmatulloh, Ramanda Fikri; Susilo, Atiq (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Vocabulary is important in English language instruction, as it is indispensable for comprehending and articulating thoughts, necessitating a diverse array of classroom learning techniques, innovative pedagogical methods, and multimedia integration, and encourages teachers to try new methods, like using songs to help students get better at words. This research focuses on the effectiveness and how well students remember the vocabulary by lyric songs counted with percentage. This research will measure the dependent variable before and after exposure to the treatment, the total vocabulary in the pre-test and post-test, to see the improvement of song lyrics and check their memorization. This study uses a quantitative approach by pre-test, treatment, and post-test conducted with 34 participants in seventh grade Junior High School students. This research found that 85% of students improved their vocabulary through song with 56,15% of improvement. It means song is an effective learning medium for learning vocabulary. It means song is an effective learning medium for learning vocabulary.